Improving thermal efficiency of hydrate-based heat engine generating renewable energy from low-grade heat sources using a crystal engineering approach. (1st May 2020) - Koyama, Ryo; Chen, Li-Jen; Alavi, Saman; Ohmura, Ryo
Abstract: The development of the eco-friendly technology generating energy will be a gradual requirement all over the world to replace thermal power releasing CO2 and nuclear power for which the wastes are disposed of with great difficultly. The hydrate-heat engine is a new cycle obtaining mechanical work from temperature differences that normally cannot generate energy, for example, heat differences between the top and bottom seawater. Although the hydrate cycle is a more sustainable power generation system than typically used Rankine cycle from the aspect of using environmental harmless working media, this new cycle has an issue as the low thermal efficiency. To increase the thermal efficiency, the performance of the hydrate-based heat engine utilizing structure II and H hydrates is theoretically evaluated for various models of low-grade heat sources. The results showed that the structure II and H hydrates formed by adding large guest molecule compounds to a second small guest gas system were effective in improving thermal efficiency. Especially, the double hydrate with Kr and cyclopentane enable the hydrate cycle to perform as efficiently as Rankine cycle, having the thermal efficiency around 3.0%, for the ocean thermal energy conversion in the temperature range from 282 K to 293 K. Highlights: First theoretically analyzed a hydrate-based heat engine using double hydrates. Calculated thermal efficiencies of the heat engine for several low-grade heat sources. Evaluated the efficiency of the heat engine comparable to that of the Rankine cycle. Revealed new dominant factors related to the thermal efficiency of the heat engine. Showed the usefulness of the heat engine with usually unused temperature differences.